Antonia's story: Bringing the past into the future. (17th February 2022) - Barden, Owen; Walden, Steven J.; Bennett, Davey; Bird, Nicole; Cairns, Stella; Currie, Rhiannon; Evans, Lynne; Jackson, Stephen; Oldnall, Emily; Oldnall, Sarah; Price, Dawn; Robinson, Tricia; et al.
Abstract: Background: This paper reports on a participatory project on the history of learning disability. The paper makes contributions to discourses on using participatory research methods with people labelled with learning disabilities, on the nature of research impact in participatory research, and on the lived experience of learning disability today. Methods: We used a two‐step methodology. The first step involved searching for and selecting archive material relating to the history of learning disability. The second step involved a series of participatory workshops. We worked collectively to systematically analyse the case history of Antonia Grandoni. Then we responded to it in a variety of creative ways. In doing so, we made connections between Antonia's life and our own. Findings: Many of Antonia's experiences seem very similar to what people labelled with learning disabilities often encounter today. These include discrimination, segregation and dehumanisation. Despite this, we very much enjoyed doing the research. As well as finding out about the history, some of us learned new skills, some of us grew in confidence, and we also made new friends. Conclusions: Participatory methods are an effective way of making digital archive material more accessible to people labelled with learning disabilities. In this project, using participatory methods revealed a lot of parallels between how we think somebody experienced learning disability in the mid‐19th century, and how it is experienced today. They also resulted in significant impact on the people doing the research. Accessible summary: This is a paper about how we researched learning disability history together. We used material in a digital archive as well as creative methods to do our research. Working this way helped us learn about ourselves, and each other's experiences of learning disability, whilst we learned about the history. This is important because people with learning disabilities have not often been able to do historical research. Research like this matters because doing it teaches us useful skills and can be empowering.